Gene therapy for neurodegenerative disorders: advances, insights and prospects - Wei Chen; Yang Hu; Dianwen Ju (Elsevier, 2020)
Gene therapy is rapidly emerging as a powerful therapeutic strategy for a wide range of neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease (HD). Some early clinical trials have failed to achieve satisfactory therapeutic effects. Efforts to enhance effectiveness are now concentrating on three major fields: identification of new vectors, novel therapeutic targets, and reliable of delivery routes for transgenes. These approaches are being assessed closely in preclinical and clinical trials, which may ultimately provide powerful treatments for patients. Here, we discuss advances and challenges of gene therapy for neurodegenerative disorders, highlighting promising technologies, targets, and future prospects.